Neuroendocrine Neoplasms of the Gastroenteropancreatic System: Pathology and Classification - Anlauf, M. (Hormone and Metabolic Research, 2011)
Neuroendocrine neoplasms (NEN) appear homogeneous in terms of morphology, but constitute a very heterogeneous group of tumors in terms of biological and clinical features. NEN may occur in any organ, but are most commonly observed in the lung and the gastroenteropancreatic system (GEP). The European Neuroendocrine Tumor Society (ENETS) developed guidelines in the last 5 years to standardize and improve the diagnosis and therapy of GEP-NEN. Taking these guidelines into account, the TNM classification of the Union for International Cancer Control (UICC) was introduced in 2009. The new GEP-NEN classification of the World Health Organization (WHO) was presented 1 year later. According to the guidelines of the ENETS, the UICC, and the WHO, the pathology classification of NEN of GEP consists of several basic components: (1) evidence of the neuroendocrine nature of the tumor, (2) histological distinction between well and poorly differentiated tumors, (3) proliferation-based grading. (4) TNM staging (including data about vascular invasion and resection margins), (5) with reference to the clinical question: evidence of hormones and biogenic amines, and (6) optional, especially in cases of initial diagnosis of NEN: expression of the somatostatin receptor type 2A. Based on these criteria, a standardized prognostic stratification of GEP-NEN can be performed in combination with other clinical parameters. The novel classifications constitute the basis for selecting the procedures of molecular and metabolic imaging as well as for tumor-specific treatments and permit comparisons of larger tumor populations. Close interdisciplinary cooperation is a prerequisite.
Keywords: grading; hormones; molecular imaging; neuroendocrine tumor; TNM classification